2001
DOI: 10.1007/s394-001-8358-x
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid in soups prepared from organically and non-organically grown vegetables

Abstract: Organic vegetable soups contained more salicylic acid than non-organic ones, suggesting that the vegetables and plants used to prepare them contained greater amounts of the phenolic acid than the corresponding non-organic ingredients. Consumption of organic foods may result in a greater intake of salicylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 13 publications
0
53
0
Order By: Relevance
“…The median contents of salicylic acid in organic vegetable soups were significantly higher (117 vs. 20) than in the compared non-organic ones (Baxter et al, 2001). Organicallygrown tomatoes also have a higher salicylic acid content than conventional ones (Rossi et al, 2008).…”
Section: Other Phytomicronutrientsmentioning
confidence: 76%
“…The median contents of salicylic acid in organic vegetable soups were significantly higher (117 vs. 20) than in the compared non-organic ones (Baxter et al, 2001). Organicallygrown tomatoes also have a higher salicylic acid content than conventional ones (Rossi et al, 2008).…”
Section: Other Phytomicronutrientsmentioning
confidence: 76%
“…56 57 Brandt et al 28 reported substantially higher contents of defence-related secondary metabolites, represented by phenolic acids; other defence compounds (tannins, alkaloids, chalcones, stilbenes, flavanones and flavanols, hop acids, coumarins and aurones), and total phenolics. The authors estimate, based on a meta-analysis of 65 papers, that if a person changes from consuming exclusively conventional fruit and vegetables to consuming the organic alternatives of the same products in the same amounts, the intake of all secondary metabolites would increase by approximately 12%, and the intake of more specifically defence-related secondary metabolites would increase by approximately 16% 28.…”
Section: Discussionmentioning
confidence: 99%
“…Whether such a difference has health-related implications remains to be shown. Baxter et al 57 showed that soups based on organically grown plants had higher content of salicylic acid than those made from non-organic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using HPLC with alkaline-or acid-hydrolysis and compound validation by MS are preferred for the construction of dietary salicylate databases. Using data from such studies (Swain et al 1985;Venema et al 1996;Baxter et al 2001), together with the application of a semi-quantitative food-frequency questionnaire (Scottish Collaborative Group food-frequency questionnaire version 7.0; Scottish Collaborative Group, 2005) for forty-one individuals (51-71 years), cautiously and provisionally provides estimates for daily intake of 9 . 9 (range 1-31) mg/d; G McNeill, G Munro and GG Duthie, unpublished results).…”
Section: Salicylates In Foods and Dietary Intakesmentioning
confidence: 99%